Surveillance and Liberty in Céline's New York, the City That Doesn't Sleep (Around) - Jennifer Willging (Studies in 20th & 21st Century Literature, 2005)
This essay focuses on Ferdinand Bardamu's account of his stay in New York City in Louis-Ferdinand Céline's bleak bildungsroman, Journey to the End of the Night (1932). In it I explore the rather surprising absence of reference to the Statue of Liberty in a text narrated by a French immigrant of sorts who spends weeks on Ellis Island and who immediately personifies the city as an androgynous, steely, and indeed statue-like woman. Applying to the text Foucault's theories on the disciplinary nature of modern western society, I suggest that it is Bardamu's suspicion that he is under unobtrusive yet constant surveillance while in the Big Apple that explains his deliberate erasure of Liberty/liberty from the skyline he paints in his narrative. I further argue that Bardamu tends to see the implacable surveillance he undergoes throughout his American adventure as feminine. That is, he identifies it as emanating principally from those cold, impenetrable, but impossibly beautiful creatures—les Américaines—that this vertical and imposing mother-city has birthed.
Keywords: Ferdinand Bardamu; Louis-Ferdinand Céline; bildungsroman; Journey to the End of the Night; Statue of Liberty; French immigrant; Ellis Island; Foucault; modern western society; western society; surveillance; Big Apple; New York City; liberty; feminine; les Américaines